2017
DOI: 10.1016/j.physletb.2017.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Knotted solutions for linear and nonlinear theories: Electromagnetism and fluid dynamics

Abstract: We examine knotted solutions, the most simple of which is the "Hopfion", from the point of view of relations between electromagnetism and ideal fluid dynamics. A map between fluid dynamics and electromagnetism works for initial conditions or for linear perturbations, allowing us to find new knotted fluid solutions. Knotted solutions are also found to to be solutions of nonlinear generalizations of electromagnetism, and of quantum-corrected actions for electromagnetism coupled to other modes. For null configura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…In particular, embedded the same null Hopfion solution in fluid dynamics, with P=0, for which the energy‐momentum tensor is Tμν=ρuμuν,and the velocity is null, uμuμ=0. As we see, in this case also we have the same condition Tμμ=0,(Tn)μν=0.n2.This suggests that we can generalize the condition to other systems.…”
Section: Symmetries and Conserved Chargesmentioning
confidence: 57%
See 1 more Smart Citation
“…In particular, embedded the same null Hopfion solution in fluid dynamics, with P=0, for which the energy‐momentum tensor is Tμν=ρuμuν,and the velocity is null, uμuμ=0. As we see, in this case also we have the same condition Tμμ=0,(Tn)μν=0.n2.This suggests that we can generalize the condition to other systems.…”
Section: Symmetries and Conserved Chargesmentioning
confidence: 57%
“…Note that a plane electromagnetic wave is also null, and one can apply such a procedure on it as well. In [], a connection of null electromagnetism with fluid dynamics was used in order to explore other ways of finding solutions in both theories.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we extend and elaborate on results already presented in the letter [27], using relations between electromagnetism and fluid dynamics to find more (time dependent) knotted solutions for both. First, we find that fluid dynamics can be rewritten in electromagnetism language, with some restrictions.…”
Section: Introductionmentioning
confidence: 68%
“…Another problem is to study the Finsler geometries corresponding to the polynomial action which implies including the constraints in the fundamental Finsler function. New generalizations of the Rañada fields have been presented recently in the literature, see e. g. [5][6][7][8] for topological solutions in the presence of the gravitational field and [9][10][11][12][13][14] for generalization to the non-linear electrodynamics. It should be interesting to generalize the construction presented in this paper to determine the Finsler geometries associated to these systems.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the topological solutions to Maxwell's equations in vacuum, firstly proposed by Trautman and Rañada in [1][2][3], has revealed so far a rich interplay between physical systems and mathematical structures which was previously unexpected in the realm of classical electrodynamics and classical field theory [4]. Since then, the subject of the topological electromagnetic fields has gain momentum with very interesting problems investigated recently, such as the existence of topological solutions of the Einstein-Maxwell theory [5][6][7][8] and of the non-linear electrodynamics [9][10][11][12][13][14]. Also, it has been shown that there are interesting mathematical structures that can be associated to the physical systems a e-mail: adina.crisan@mep.utcluj.ro b e-mail: ionvancea@ufrrj.br (corresponding author) with topological electromagnetic fields and play an important role in their dynamics, such as twistors [15], fibrations [16] and rational functions [17,18] (see for recent reviews [19][20][21]).…”
Section: Introductionmentioning
confidence: 99%